The World Crises in Hegel’s Dialectic Thinking & the Current Contradictions Confronted Europe - Skoulas, Georgios; Skoula, Despoina (Dia-noesis: A Journal of Philosophy, 2024)
The research objective of this paper emanates from a reasonable anxiety regarding the direction of things in the present world scene. For that, the Hegelian notion of the world crises is necessary to be traced in order to comprehend better the course of world economy and the contradictions that the EU is confronted with today. The main interest is focused on: the shaped order of the world, the political actions and strategies that are implemented by the dominant forces of the planet, the prospects and objectives that emerged in the European Union. This way, the political theory of neo-liberalism is traced in order to compare the results of the political actions which facilitated the increasing tendencies of the globalization. Yet, the prospects and possible developments of the European Union are studied carefully, while the latter is found today in the direction and stage of its endeavors of political integration. This attempt is made more or less to strong unification of EU, because with one united Europe it is possible to liberate itself from the tenet of neo-liberalism. It means, that EU could possibly line up one human, just and democratic alternative solution to the anarchist capitalism of the hegemonic forces of the West as well as to the authoritarian Asiatic capitalism. The research then, is to highlight the elements that compose the deepening for the real political unification of the European Union, without overseeing the obstacles that appear in that venture. Emphasis is given to the international economic system and to the neo-liberalist ideological doctrine which restricts the dynamic of the political integration.